INTRODUCTION OF BLASCHKE DISTRIBUTIONS AND APPROXIMATION OF DISTRIBUTION IN \(D'\) BY A SEQUENCE OF FINITE BLASCHKE DISTRIBUTIONS - Manova-Eraković, Vesna (Matematichki Bilten, 2000)
In this work Blaschke distributions are defined and used to approximate a distribution in \(D'\).